GPS-based highway toll collection system: Novel design and operation - Tan J.Y.; Ker P.J.; Mani D.; Arumugam P. (Cogent OA, 2023)
The requirement for vehicles to halt for toll fee payment results in traffic congestion and reduces fuel efficiency. In this paper, hardware and software designs were involved to develop a GPS-based highway toll collection system. The system utilised the Raspberry Pi 2 as the microcontroller. Additional electronic modules such as GPS module, LCD module, speaker, wireless Wi-Fi router modem and wireless Wi-Fi adapter were included to perform specific tasks. The system utilised GPS coordinates to track vehicle and toll fees were incurred at predefined points. The travel summary was recorded in the online database. Furthermore, an automatic delay time adjustment system was studied and was implemented to reduce the power consumption of the system without compromising the accuracy. A personal cloud server was configured to allow online access of travel logs. The developed system promises motorists a smooth travel journey and eliminates the construction of expensive toll booths. 2017 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.